An Unusual Left Upper Quadrant Mass: A Bronchopulmonary Foregut Malformation. (27th February 2013) - McDermott, R. L.; Kavanagh, D. O.; Bartosik, W.; Quinn, C.; O'Connell, P. R.
Abstract : We report a case of a lady who presented with epigastric discomfort. Physical examination revealed a large left upper quadrant mass filling the left upper quadrant. Following extensive preoperative evaluation, she underwent resection of this 9 × 10 × 11 centimeter mass with en bloc excision of a portion of the left hemidiaphragm. She made an uneventful postoperative recovery. Histopathology revealed a bronchopulmonary foregut malformation with pulmonary sequestration. This developmental anomaly of the foregut typically occurs in the thoracic cavity; however, it can occur below the diaphragm. Herein we report a case and a detailed review of the embryology, clinical features, and management of these extremely rare clinical entities.